Nurse assistance to women with postpartum depression: a narrative review of the literature (Research, Society and Development, 2023)
Objective: to identify the role of nurses in assisting women with postpartum depression. Methodology: Integrative Literature Review. The Virtual Health Library (VHL) databases and the Google Scholar search engine were used. Results: 09 articles were found, recently published, in the last ten years, that dealt specifically with the proposed theme. Final considerations: Socioeconomic aspects were highlighted as relevant to the occurrence of postpartum depression. The role of nursing concerns humanized care, with a view to perceiving signs of depression, strengthening, and empowering the puerperal woman, and maintaining continuing education to learn about aspects of comprehensive care.